Representaciones Sociales De Los Adolescentes Sobre El Embarazo A Temprana Edad (2023)
The present research aimed to analyze the social representations held by 5 teenagers from the municipality of Tuluá, in the third district, regarding early pregnancy. These were assessed through the dimensions of information, figurative or image dimension, symbolic dimension, and affective dimension proposed by Moscovici. Furthermore, sub-areas such as socio-familial, motional, and educational aspects were also evaluated. In this regard, the findings obtained revealed that pregnancy represents a situation of high responsibility for both the teenagers and their families